The role of Iron on breast cancer stem-like cells - Ozer, U (Cellular and Molecular Biology, 2016)
Iron is a fundamental nutrient that enables the functions of vital enzymes involved in cell replication, metabolism and growth. Cancer cells contain higher systemic iron levels relative to normal cells. In breast cancer cells, human epidermal growth factor receptor 2 (HER2) is overexpressed more than 30% of normal and its poorly prognosis results in elevated the proportion of cancer stem cells (CSCs) which are the main drivers in cancer recurrence. Finding a relation between increases of iron levels, HER2 expression and CSC population may provide new tools for breast cancer therapy. In this study, therefore, iron dependency in HER2 overexpression and CSC survival is examined in breast cancer cell line, MCF7. It has shown that cells overexpressing HER2 require iron more than their vector counterparts and HER2-increased CSCs are vulnerable to iron chelation. Additionally, this sensitivity of CSCs to iron reduction is obviously indicated in various breast cancer cell lines; HCC1954, MDA-MB-435 and Hs578T. Finally, the concept is also shown in neoplastically transformed breast cancer cell line, HMLER. Altogether, this study demonstrates that iron depletion causes toxicity for CSCs.